Faktor-Faktor Yang Mempengaruhi Intensi Berwirausaha Pada Mahasiswa Prodi Agribisnis Universitas Syiah Kuala - Indah Suci Ramadhani; Agus Nugroho; Fajri Jakfar (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
Entrepreneurship is very important for the development of a country. This study aims to determine how the impact of entrepreneurship education on entrepreneurial intentions and to determine the factors that influence entrepreneurial intentions in Agribusiness students at Syiah Kuala University. Respondents taken in this study amounted to 77 respondents using the Taro Yamane formula and simple random sampling technique. The data that has been obtained is processed using ordinal logistic regression. The results of the analysis showed that the variables of entrepreneurship education and social media had a significant effect on students' intentions to become entrepreneurs. However, for several other variables such as gender and parental occupation, there was no significant effect on students' intentions to become entrepreneurs.